2009
DOI: 10.3399/bjgp09x453431
|View full text |Cite
|
Sign up to set email alerts
|

Identification of UK sickness certification rates, standardised for age and sex

Abstract: BackgroundThere is growing interest in tackling the perceived 'sick note' culture in the UK. AimThe aim of this paper was to report the rates of sickness certification in a UK population, using sick certification rates as a precursor to addressing fitness for work. MethodElectronic records from all 14 practices included in the Keele GP Research Network were reviewed; all sickness certification records from 2005 were retrieved and corresponding consultation records were examined. Participants were 148 176 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 18 publications
1
20
1
Order By: Relevance
“…The highest proportion of unfit‐for‐work certificates were written for workers with a MHC, followed by fractures, other traumatic injuries, back pain and strains, musculoskeletal injuries and diseases, and other diseases. Recent studies in the United Kingdom have also shown that GPs are more likely to issue unfit‐for‐work certificates for patients with MHCs than other conditions 9 , 10 . Conversely, GPs in our study were more likely to certify workers with other diseases as suitable for alternative duties than those in other categories.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The highest proportion of unfit‐for‐work certificates were written for workers with a MHC, followed by fractures, other traumatic injuries, back pain and strains, musculoskeletal injuries and diseases, and other diseases. Recent studies in the United Kingdom have also shown that GPs are more likely to issue unfit‐for‐work certificates for patients with MHCs than other conditions 9 , 10 . Conversely, GPs in our study were more likely to certify workers with other diseases as suitable for alternative duties than those in other categories.…”
Section: Discussioncontrasting
confidence: 68%
“…Evidence that GP sickness certification practices vary according to worker characteristics is growing. A common finding is that GPs are more likely to certify workers with mental health conditions (MHCs) as unfit for work than those with physical conditions 9 , 10 . Risk factors for longer duration of work incapacity include older age, social deprivation, and presence of mild and severe MHCs 11 .…”
mentioning
confidence: 99%
“…As described in the authors’ previous work and in results from other studies, cases of mental ill-health were responsible for the highest proportion of fit-notes issued, followed by musculoskeletal disorders 4 5 6. ‘May be fit’ advice was less frequently included on fit-notes issued to patients with psychological diagnoses, and this is consistent with results examining the fit-note advice offered to patients in other work.…”
supporting
confidence: 86%
“…Many studies report on the rate of certification but are unable to collect information on the length of absence 6 7. Research on the length of sickness absence in the UK has been difficult largely due to the lack of routinely collected data at general practice level 4.…”
mentioning
confidence: 99%
“…The analyses were controlled for sex, employment category and hours worked weekly. 12 19 To gain more insight into the impact of chronic disease on sick leave, the analyses were additionally controlled for this factor.…”
Section: Methodsmentioning
confidence: 99%